Fanta Product's New Packaging Study of Buying Interest Teenage Consumers in Semarang - Callista Chairani Wulandari; I Made Bayu Dirgantara (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The food and beverage industry in Indonesia is growing rapidly in the modern era. One of them is Fanta, as one of the carbonated beverage products. With so many competitors continuing to emerge, Fanta made innovations by creating new packaging that is 'twisted'. In fact, Fanta is considered to have the best performance in the Fizzy Drinks Category in the last three years after the launch of its new packaging.  The purpose of this study is to find out if there is any influence from Fanta packaging changes with buying interest. The population in this study was as many as 40 subjects who had already consumed Fanta, but had never bought Fanta with new packaging. Sampling techniques use questionnaires with simple random sampling techniques. This research uses the experimental design of True Experimental Design with the Posttest Only Control Group Design method.  The results showed that packaging and its variables such as shapes, images, colors, logos, and labels have a positive and significant influence on buying interest.